1983
DOI: 10.1056/nejm198306303082606
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine and Tranexamic Acid in the Treatment of Acute Upper-Gastrointestinal-Tract Bleeding

Abstract: We studied the effects of tranexamic acid (an antifibrinolytic agent) and cimetidine on acute upper-gastrointestinal-tract bleeding in a double-blind randomized placebo-controlled trial in 775 patients with hematemesis or melena or both. Mortality was significantly reduced in patients receiving either tranexamic acid (mortality, 6.3 per cent) or cimetidine (7.7 per cent), as compared with patients receiving placebo (13.5 per cent) (P = 0.0092 for tranexamic acid vs. placebo, P = 0.045 for cimetidine vs. placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
79
0
5

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 13 publications
0
79
0
5
Order By: Relevance
“…Rapid and potent neutralization of intragastric pH with acid inhibitors is required to cure acid-related diseases. Intragastric pH during treatment is associated with cure rates of peptic ulcers, 43 GERD, 44 and aspirin-induced gastroduodenal mucosal injury. 45 Further, treatment for eradication of H. pylori fails when acid secretion is not sufficiently inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and potent neutralization of intragastric pH with acid inhibitors is required to cure acid-related diseases. Intragastric pH during treatment is associated with cure rates of peptic ulcers, 43 GERD, 44 and aspirin-induced gastroduodenal mucosal injury. 45 Further, treatment for eradication of H. pylori fails when acid secretion is not sufficiently inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Intragastric pH during treatment is associated with the cure rate of treating peptic ulcers [23], GERD [24] and aspirin-induced gastrointestinal mucosal injury [25]. Further, the eradication treatment for H. pylori infection fails if the inhibition of acid secretion during therapy is insufficient [26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 27 published trials on the use of H 2 -receptor antagonists in patients with suggested that these drugs only marginally reduced the need for surgery and mortality compared to other medical therapies or placebo [108]. A study by Barer et al [106] concluded that although H 2 -receptor antagonists are helpful in healing peptic ulcers, they do not reduce the transfusion requirements, incidence of recurrent bleeding or the need for surgery in patients presenting with UGI haemorrhage. However, H 2 -receptor antagonists are still routinely used in the initial management of patients with acute UGI bleeding, even though they provide little or no immediate benefit [109].…”
Section: Histamine (H 2 )-Receptor Antagonists and Proton Pump Inhibimentioning
confidence: 99%
“…omeprazole, which are more potent inhibitors of acid secretion that the H 2 -receptor antagonists, were introduced later. However, neither H 2 -antagonists nor PPIs reduce gastric/mucosal blood flow and hence are unlikely to be useful in the control of bleeding [43,106,107]. A meta-analysis of 27 published trials on the use of H 2 -receptor antagonists in patients with suggested that these drugs only marginally reduced the need for surgery and mortality compared to other medical therapies or placebo [108].…”
Section: Histamine (H 2 )-Receptor Antagonists and Proton Pump Inhibimentioning
confidence: 99%